2019
DOI: 10.1007/s10620-019-05800-6
|View full text |Cite
|
Sign up to set email alerts
|

Office-Based Weight Loss Counseling Is Ineffective in Liver Transplant Recipients

Abstract: Background Weight gain after liver transplantation (LT) is a predictor of major morbidity and mortality post-LT; however, there are no data regarding weight loss following LT. The current study evaluates the effectiveness of standard lifestyle intervention in LT recipients. Methods All adult LT recipients with body mass index (BMI) ≥ 25 kg/m 2 who followed up in post-LT clinic from January 2013 to January 2016 were given standard lifestyle advice based on societal recommendations which was reinforced at 24 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…[23] Indeed, previous experience shows that standard office-based weight-loss counseling is ineffective in this population. [24] Finally, a role of immunosuppression cannot be discarded as using everolimus has also been associated with lower post-LT weight gain. [25] Indeed, the contribution of immunosuppression to our results is clear considering the different CV profiles of immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Indeed, previous experience shows that standard office-based weight-loss counseling is ineffective in this population. [24] Finally, a role of immunosuppression cannot be discarded as using everolimus has also been associated with lower post-LT weight gain. [25] Indeed, the contribution of immunosuppression to our results is clear considering the different CV profiles of immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…30 The increased incidence of posttransplant diabetes mellitus is associated with a worse outcome of LT. 31 Currently, our institution manages post-LT obese patients with active weight-loss programs, including standard lifestyle advice, dietary modification, and physical therapy; however, emerging evidence showed that office-based lifestyle intervention was ineffective in achieving weight loss in LT recipients. 32 Thus, even our study showed the long-term graft and patient survival of the class III obesity group was comparable with other groups, we should consider more aggressive post-LT intervention to prevent long-term BMI increase for the class III obesity group. This study has several limitations.…”
Section: Discussionmentioning
confidence: 56%
“…However, emerging evidence showed that o ce-based lifestyle intervention was ineffective in achieving weight loss in LT recipients. 33 Thus, even our study showed the long-term graft and patient survival of the class obesity group was comparable with other groups, we should consider more aggressive post LT intervention to prevent long-term BMI increase for the class obesity group. This study has several limitations.…”
Section: Discussionmentioning
confidence: 57%